ANALISIS KEBERTERIMAAN SISTEM INFORMASI AKUNTANSI PERUSAHAAN MANUFAKTUR DI INDONESIA - Siregar, Cantika Sari; Permatasari, Ika; Pujiono, Pujiono; Ilham, Romi (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2021)
Accurate Accounting Software is the best financial and accounting application with the most brands used in Indonesia. With the presence of this Accounting Information System (AIS), the study aims to determine the behavioral intentions of companies in implementing the Accurate Accounting Software system with the UTAUT (Unified Theory of Acceptance and Use of Technology) model. This study uses a quantitative approach with a population of 14 manufacturing companies in Indonesia and a sample of 190 respondents. Confirmatory Factor Analysis using the SEM-PLS algorithm with PLS Warp software. Descriptive analysis results show that the majority of respondents have high levels of performance expectations, effort expectations, social influence, facilitation conditions, and user behavior. In contrast, the level of the behavioral intention of most respondents is moderate. Spearman's correlation test results indicate that performance expectations, effort expectations, social influence, and facilitation conditions have a significant correlation (p-value <0.01) on behavioral intentions. Likewise, facilitating conditions and behavioral intentions have a positive and significant correlation with user behavior (p-value <0.05)